The economic value of the Colombo Public Library, Sri Lanka: contingent valuation approach. (3rd May 2016) - Kaluthanthri, Prathap Chandima; Edirisinghe, Janakie
Abstract: Net Revenue of a public library is not an indicator of the true value of services rendered by a public library to the wider society. The peoples' perception of the service of the library or economic value is the true value of the library. The Contingent Valuation Method (CVM) used to assess the economic value of a public library which is not a service in the free market economy. This study employs CVM: a branch of the Stated Preference Method to measure the economic value of the Colombo Public Library (CPL) Sri Lanka. The payment vehicle is a Trust Fund. The logistic regression has been applied to estimate the Willingness to Pay (WTP) of citizens which elicited through single bound dichotomous choice question with onetime payment option. The WTP for the population is aggregated by using mean probabilistic logic WTP of the sample. The study found that annualized economic value of the CPL is higher than its total capital and recurrent expenditure per year. Thus, continuation of public funding is acceptable even CPL makes financial losses to the Colombo Municipal Council.